Lepidaploa restingae (Asteraceae: Vernonieae), a new species from Northeastern Brazil - Soares, Gleison; Loeuille, Benoît (Phytotaxa, 2021)
Lepidaploa restingae, a new species from the restinga vegetation in Northeastern Brazil, is described and illustrated. This new species differs from morphologically related species by the branch indument, leaf morphology, number of phyllary series and corolla lobe indument. Taxonomic comments, a distribution map and a preliminary conservation status for the new species are provided.